192k views
3 votes
Please find the derivative of
\displaystyle \frac{e^{(3)/(x)}}{x^2}. Show all work necessary - thanks!

User PSpeed
by
5.3k points

2 Answers

3 votes

Answer:


\displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2e^{(3)/(x)}}{x^3}

General Formulas and Concepts:

Pre-Algebra

  • Splitting Fractions

Algebra I

  • Terms/Coefficients
  • Factoring
  • Exponential Rule [Multiplying]:
    \displaystyle b^m \cdot b^n = b^(m + n)

Calculus

Derivatives

Derivative Notation

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Derivative Rule:
\displaystyle (d)/(dx) [e^u]=e^u \cdot u'

Quotient Rule:
\displaystyle (d)/(dx) [(f(x))/(g(x)) ]=(g(x)f'(x)-g'(x)f(x))/(g^2(x))

Explanation:

Step 1: Define


\displaystyle \frac{e^{(3)/(x)}}{x^2}\\f(x) = e^{(3)/(x)}\\g(x) = x^2

Step 2: Differentiate

  1. Quotient Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{(d)/(dx)[e^{(3)/(x)}] \cdot x^2 - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  2. Derivative Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{e^{(3)/(x)} \cdot (-3)/(x^2) \cdot x^2 - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  3. [Simplify] Multiply:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - (d)/(dx)[x^2] \cdot e^{(3)/(x)}}{(x^2)^2}
  4. Basic Power Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2x^(2-1) \cdot e^{(3)/(x)}}{(x^2)^2}
  5. [Simplify] Subtract Exponents:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2x \cdot e^{(3)/(x)}}{(x^2)^2}
  6. [Simplify] Multiply:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{(x^2)^2}
  7. [Simplify] Exponent Rule:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{x^(2 + 2)}
  8. [Simplify] Add Exponents:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)} - 2xe^{(3)/(x)}}{x^4}
  9. [Simplify] Fraction Split:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2xe^{(3)/(x)}}{x^4}
  10. [Simplify - 2nd Fraction] Cancel Like Terms:
    \displaystyle (d)/(dx)[\frac{e^{(3)/(x)}}{x^2}] = \frac{-3e^{(3)/(x)}}{x^4} - \frac{2e^{(3)/(x)}}{x^3}

And we have our final answer!

User Janne Valkealahti
by
5.5k points
6 votes

Hello! :)


\large\boxed{\frac{-e^{(3)/(x)} (3 + 2x )}{x^(4)}}

Find the derivative using the quotient rule:


(f(x))/(g(x)) = (g(x) * f'(x) - f(x) * g'(x))/((g(x))^(2))

In this instance:


f(x) = e^{(3)/(x) }\\\\g(x) = x^(2)

Use the following properties to find the derivative of f(x) and g(x):


e^(u) = u' * e^(u)\\\\x^(n) = nx^(n-1)

Use the quotient rule:


\frac{x^(2) * (e^{(3)/(x)} * (-3x^(-2))) - e^{(3)/(x)} * 2x }{(x^(2) )^(2)}

Simplify the numerator:


\frac{(e^{(3)/(x)} * (-3)) - e^{(3)/(x)} * 2x }{(x^(2) )^(2)}

Factor out
e^{(3)/(x)}


\frac{e^{(3)/(x)} (-3 - 2x )}{x^(4)}

Factor out -1 from the numerator:


\frac{-e^{(3)/(x)} (3 + 2x )}{x^(4)}

And we're done! Thanks for posting the question to my 1000th answer!

User Mohammad Zargarani
by
5.3k points